Higher education governance and policy change in Western Europe international challenges to historical institutions - Dobbins, Michael 1975-; Knill, Christoph 1965- (Palgrave MacMillan, 2014)
This book provides a systematic, comparative analysis of the impact of 'soft Europeanization' on higher education governance in Western Europe. Focusing on the four countries that initiated the Bologna Process -- Italy, France, Germany and the United Kingdom, Michael Dobbins and Christoph Knill explore how the tensions between historical legacies and transnational forces of change have impacted policy pathways. Higher Education Governance and Policy Change in Western Europe tackles the key question of whether or not the Europeanization of the policy field has pushed Western European higher education systems towards a common governance model
1. Introduction: Higher Education Governance between Historical Roots and Transnational Convergence Pressures -- 2. Theoretical Framework: National Higher Education Policies between Transnational Communication and Institutional Path-Dependence -- 3. France: More State, More Market and More Humboldt? -- 4. Italy: The "Outsmarted" State? -- 5. Great Britain: Policy "Doubling-Down" as a Response to Transnationalization? -- 6. Germany: From Humboldtism to "Constrained Marketization" -- 7. Comparative Conclusions
Keywords: Geschichte 2000-2012; Higher education and state / European Union countries; Education, Higher / Law and legislation / European Union countries; Recht; Hochschulbildung; Bildungspolitik; Europäische Union. Mitgliedsstaaten; Westeuropa